Penegakan Hukum Terhadap Tindak Pidana Pencurian Kendaraan Bermotor Studi Kasus Kota Medan - Lukman Hakim; Si Putri A Pramudinta; Andhika Bayu Pranata (CV. ITTC INDONESIA, 2025)
The purpose of this study was to determine the law enforcement of the crime of the theft of motor vehicles (curanmor) is one of the important efforts in maintaining security and public order. This research uses quantitative methods (internet research and court decisions) and research. The crime of curanmor, which often occurs in various regions, causes significant material losses and affects the sense of public security. Law enforcement against this crime involves a series of actions ranging from investigation, arrest, confiscation of evidence, to the judicial process. This research examines the effectiveness of law enforcement carried out by the police, obstacles faced in the handling process, and solutions that can be implemented to improve the effectiveness of handling curanmor crimes. It was found that constraints such as limited personnel, lack of supporting technology, and organized networks of perpetrators are the main factors that hinder law enforcement efforts. The proposed recommendations include increasing cooperation between agencies, optimizing the use of technology, and improving the quality of police human resources to face the challenges of increasingly complex crimes.